Synthesis of phenacylmethacrylate: Its characterization and polymerization - Ozdemir, E; Soykan, C; Coskun, M; Ahmedov, MA (Marcel Dekker Inc, 1997)
Phenacylmethacrylate (PAMA), a new monomer containing two carbonyl groups (C=O), was obtained from phenacyl chloride and sodium methacrylate. The homopolymer of PAMA and its copolymer with styrene were prepared in dioxane by using benzoylperoxide (Bz(2)O(2)) as initiator. IR, H-1-NMR and C-13-NMR techniques were used to identify the structure of the monomer and polymers. The density of monomer, homopolymer and copolymer were found to be 1.13; 1.35 and 1.10 gr/ml respectively. Also, limit viscosity numbers, solubility parameters, glass transition and decomposition temperatures of polymers were determined.
Keywords: phenacylmethacrylate; poly(phenacylmethacrylate); poly(phenacylmethacrylate-co-styrene); solubility parameter; thermal analysis